Stroke and cerebrovascular disease in childhood - Ganesan, Vijeya; Kirkham, Fenella J. (International review of child neurology., 2011)
"The field of stroke and cerebrovascular disease in children is one in which there has been much recent research activity, leading to new clinical perspectives. This book for the first time summarises the "state of the art" in this field. A team of eminent clinicians, neurologists and researchers provide an up-to-the-minute account of all aspects of stroke and cerebrovascular disease in children, ranging from a historical perspective to future directions, through epidemiology, the latest neuroimaging techniques, neurodevelopment, co-morbidities, diagnosis and treatment. The authors? practical approach to the clinical problems makes this essential reading for practising clinicians. It will also be of interest to researchers in the field"--Page 4 of cover